A parallel image encryption algorithm using intra bitplane scrambling - Song, Wei; Fu, Chong; Zheng, Yu; Tie, Ming; Liu, Jun; Chen, Junxin (Mathematics and computers in simulation, 2023)
More and more privacy-sensitive images have been produced daily. Chaotic encryption guarantees that only the targeted receiver can obtain the raw image. Many works perform encryption on bit-level for better permutation but incur an unbearable time consumption caused by generating additional 3D coordinates. High-dimensional chaotic system, suitable for encrypting images, needs to iterate repeatedly for several rounds, resulting in low encrypting efficiency. This paper proposes a parallel image encryption algorithm using intra bitplane scrambling. Four threads are utilized to encrypt the images in bit-level during the permutation, where each thread scrambles two bitplanes. In diffusion, we build multiple threads to generate keystream segments to reduce encryption time. We make cryptographic analyses and compare the encryption speed with the advanced works, demonstrating that our scheme is secure and efficient. •The proposed parallel bit-level permutation algorithm offers a good trade-off between efficiency and effect.•To accelerate the keystreams generation in diffusion stage, multi-threading technology is used to generate them in parallel.•The results of security analyses show the proposed algorithm has high efficiency compared with other state-of-the-art algorithms.